A three-dimensional model for thermoelectric generator and the influence of Peltier effect on the performance and heat transfer. (25th March 2018) - Liao, Mingjian; He, Zhu; Jiang, Chengpeng; Fan, Xi'an; Li, Yawei; Qi, Fengsheng
Highlights: A 3-D model for thermoelectric modules which consisting of 127 thermocouples is developed. An experiment was carried out to validate the simulation. Influence of Peltier effect on the performance and heat transfer is investigated. The Peltier effects are proved to be more remarkable for weak heat transfer boundary conditions. Abstract: Thermoelectric generator has been considered as a promising device to recover industrial waste heat for electricity generating. To figure out the heat transfer and electric conduction processes in thermoelectric generator, a three-dimensional numerical model has been built up which consists of 127 thermocouples. The open-circuit voltage, internal resistance, and output power have been studied by numerical simulation. All calculation results are in good agreement with the experimental results, and the maximum deviation is less than 6%. Due to the influence of Peltier effect, both heat flow and equivalent thermal conductivity increases by 30.2% when temperature difference between the hot and cold side is 170 °C and the thermoelectric generator reaches its maximum power output. In addition, the Peltier effect has been investigated when the convective heat transfer boundary conditions are applied. The results showed that the effective temperature difference was raised to 13.6 °C (a 10.2% increase) and maximum output power was raised to 0.59 W (a 14.8% increase) for the thermoelectric generator model with a fin height of 100 mm when compared with that without fins. Besides that, the radio of load resistance to internal resistance decreased from 1.31 to 1.14.